2020
DOI: 10.1002/jcop.22404
|View full text |Cite
|
Sign up to set email alerts
|

Valid or voodoo? A qualitative study of attorney perceptions of risk assessment in sentencing and plea bargaining

Abstract: Prior research largely has explored judicial perceptions of risk assessment in sentencing. Little is known about how other court actors, specifically, prosecutors and defense attorneys, perceive risk assessments in the sentencing process. Here, we report a qualitative study on the use of risk assessment by prosecutors and defense attorneys in Virginia. A prior survey (n = 70) pointed to a statistically significant difference in how prosecutors and defense attorneys view the role of recidivism risk in sentencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…This finding was consistent with previous studies on the judicial perception of risk assessment at both sentencing (Metz et al, 2019;Monahan et al, 2018) and pretrial stages (DeMichele et al, 2018). Participants who were skeptical of an actuarial instrument were less likely to trust the results of a risk assessment, meaning that relevant risk information may be ignored in practice (Metz et al, 2019(Metz et al, , 2020.…”
Section: People Who Use Them Don't Believe They Are Validsupporting
confidence: 90%
See 4 more Smart Citations
“…This finding was consistent with previous studies on the judicial perception of risk assessment at both sentencing (Metz et al, 2019;Monahan et al, 2018) and pretrial stages (DeMichele et al, 2018). Participants who were skeptical of an actuarial instrument were less likely to trust the results of a risk assessment, meaning that relevant risk information may be ignored in practice (Metz et al, 2019(Metz et al, , 2020.…”
Section: People Who Use Them Don't Believe They Are Validsupporting
confidence: 90%
“…On the whole, risk assessment instruments are more accurate than clinical judgment when it comes to predicting recidivism risk (Andrews et al, 2006;Grove et al, 2000;Latessa & Lovins, 2010). But research on perceptions of risk assessment in sentencing suggests that the main consumers of these instruments-judges, prosecutors, and defense attorneys-are skeptical of their predictive validity (Metz et al, 2019(Metz et al, , 2020Monahan et al, 2018). A recent study of prosecutors and defense attorneys by Metz et al (2020) found that while there was support for the use of risk assessment as a strategy for reducing mass incarceration, participants were practically unanimous in their objection to several risk factors used by the NVRA instrument-particularly gender and age.…”
Section: People Who Use Them Don't Believe They Are Validmentioning
confidence: 99%
See 3 more Smart Citations